The effect of inspiratory muscle training and royal jelly supplement on lipid metabolism in smoking addicts - Pancar, Serkan; Pancar, Zarife (Progress in Nutrition, 2020)
Study Objective: This study aimed to investigate the effects of inspiratory muscle training and royal jelly supplementation on lipid metabolism in smoking addicts. Methods: A total of fourty males aged between 20-22 years were included in the study. Before the study, the groups who were addicted to smoking were divided into four groups as the control group (n: 10), royal jelly supplement group (n: 10), IMT group (n: 10), and royal jelly + IMT group (n: 10). Blood samples were taken from all groups for analysis of cholesterol, triglyceride, HDL, LDL levels. Groups were made to perform respiratory muscle training through an inspiratory muscle training device with 40% of their MIP values. Groups supplemented with royal jelly were provided with 1000 mg/day royal jelly supplied in glass vials. The training sessions were carried out at the same time every day for four weeks / five days. Results: A statistically significant difference was found in favor of the final test in royal jelly, inspiratory muscle exercise, royal jelly + IMT groups (p <0.05). Conclusion: It can be said that royal jelly and inspiratory muscle exercises affect blood lipids.